(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Aquaculture especially shrimp farming has significant contribution to the economy of Bangladesh. The southwest coastal area is more prominent for commercial shrimp farming due to its auspicious environment, higher economic returns, nutrition value and for employment opportunity. The present study estimates the socioeconomic status and financial profitability of small-scale shrimp farming in selected areas of Khulna district. One hundred (100) shrimp farmers were selected and data were collected through direct interview method. Financial profitability was analyzed from the different point of view. The study revealed that about 35% farmers lie in prime working age group. Most of the farmers completed primary level of education while a few of them were illiterate. Family size of 65 % farmer’s was medium and 40% farmer’s main occupation was shrimp farming. Study also revealed that gross profit margin was high i.e. 59% indicating that farmers did well in managing their farm and farmers has more to cover for operating, financing and other cost. Break-even price for the small scale shrimp worked out Tk. 311 per kg while break-even production was found 155 kg per acre. Benefit cost ratio and net profit margin were found more than one and positive respectively, indicated that small scale shrimp farming was commercially profitable. The research concludes that there is ample scope and possibility for sustaining and developing the small scale shrimp farming in the coastal area of Bangladesh. J. Bangladesh Agril. Univ. 16(1): 104-110, April 2018